Designing Research Data Management Services Based on the Research Lifecycle – A Consultative Leadership Approach. Issue 3 (3rd July 2017) - Yu, Fei; Deuble, Rebecca; Morgan, Helen
Abstract: Research data are a primary research output. Research Data Management (RDM) involves a complex and varying set of processes at each stage of research. Integrated RDM support services can assist researchers to manage their data proactively, and thereby, comply with data-sharing requirements from funding agencies and journal publishers. The strategic long-term benefits of supporting RDM practice by researchers include, increasing individual and institutional research reputations as trusted providers of data. Establishing RDM support services across large academic institutions requires input from multiple organisational units. The library is well positioned to lead this effort, having reach and influence across the institution. The RDM team is able to maximise the benefits for researchers by leading support services in consultation with multiple units across the university. This paper gives an overview of University of Queensland (UQ) Library RDM services provided in the planning and preparing, conducting, archiving, publishing and disseminating stages, using a research lifecycle model. It details the strategies in designing and delivering RDM services, which include preparing guides, designing training programmes for faculty librarians and researchers and engaging stakeholders within and external to the university. We present the impact of these services to-date as an informal self-assessment.